PRINSIP ITIKAD BAIK BERDASARKAN PASAL 251 KUHD DALAM ASURANSI KERUGIAN - Purwiyantiningsih, Eti (Faculty of Law, Universitas Jenderal Soedirman, 2008)
Everybody has their own risk with their life or their own. The best way to avoid the risk is by sending the risk to another party which has capable to hande it, throught insurance agreement. This insurance has many purposes such has taken over the risk to others. In insurance the participant has obligation regulation in 251 KUHD in which determined that all of the statement both true or false or all of the condition has known by participant as a reflection of honesty by participant, it can will not an agreement based on the same qualification it there is know by participant the agreement will be canceled. In the indemnity insurance as 251 KUHD there is no fully application because there is still touty at the good faith, it means that the agreement will cancel because of no good faith from the participant, therefore it will be canceled Kata kunci : itikad baik dan asuransi kerugian